Karakterisasi Enzim Amilase Dari Isolat Khamir Hasil Fermentasi Biji Kopi Robusta (Coffea canephora) - Sari, Indah Permata; Patang, Patang; Indrayani, Indrayani (Jurnal Pendidikan Teknologi Pertanian, 2024)
This study aims to determine isolate yeast spontaneously fermented Robusta coffee beans which are amylolytic and to determine the effect of incubation time, optimum pH and temperature on amylase activity. This study used RAL (Completely Randomized Design). The yeast isolates used were selected using 1% starch + 2% agar media to determine their amylolytic abilities. The isolate that produces the highest clear zone will proceed to the optimum incubation time determination stage which is divided into 6 levels, namely 24, 48, 72, 96, 120 and 144 hours with 3 repetitions. Every 24 hours the total yeast count was carried out. The optimum incubation time is used as one of the conditions in the characterization of the optimum pH and temperature of the amylase enzyme. The selected samples were then characterized at pH (4,5,6,7 and 8) and at temperature (30℃, 40℃, 50℃ and 60℃) to determine the optimum pH and temperature. The data analysis technique used was analysis of variance (ANOVA) followed by Duncan's test using SPSS Version 22. The results of this study indicated that 4 of the 7 yeast isolates involved in the spontaneous fermentation of Robusta coffee beans had amylolytic properties, namely isolates K24I3, K24I4, K24I6 and K24I7. The selection results showed that the yeast isolate K24I6 produced the highest clear zone with a diameter of 7.83 mm. The optimum incubation time for amylase enzyme from yeast isolate K24I6 was 24 hours with enzyme activity of 19.91 U/ml. The optimum yeast isolate amylase enzyme at pH 6 is 20.00 U/ml and the optimum temperature is 40℃ with enzyme activity of 19.98 U/ml.